Analisis Pemahaman Masyarakat Desa Pasirmunjul Sukatani Purwakarta Pada Bank Syariah - Sulistianingsih, Sulistianingsih; Jalaludin, Jalaludin; Saepudin, Ahmad (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
Based on field observations in Pasirmunjul Village, Sukatani, Purwakarta, a number of issues were identified that reflect the suboptimal role of Islamic banks in the economic life of the community. First, limited physical access to Islamic financial institutions means that people have to travel long distances to the city center to conduct transactions. Second, the large number of majelis taklim (Islamic study groups) has not been utilized as a medium for educating people about the Islamic banking system. Third, the majority of the community are still customers of conventional banks due to the lack of information and socialization about Islamic banks. Fourth, MSME players in this village still apply for capital through conventional banks because it is difficult to reach Islamic financial institutions. This condition shows a gap between the potential of Islamic values that live in the community and the implementation of the Islamic financial system in their economic practices. The purpose of this study is to determine the knowledge and understanding of the community of Pasirmunjul Sukatani Purwakarta Village regarding Islamic banks. This study uses a qualitative descriptive method, with primary data obtained from interviews and observations with village officials and the community of Pasirmunjul Sukatani Purwakarta Village, involving 28 informants. The conclusion of this study is that the knowledge of the people of Pasirmunjul Sukatani Purwakarta Village about Islamic banks is still limited to knowing that Islamic banks exist, but they do not clearly understand the mechanisms and operations of Islamic banks, nor do they know the products and services offered by Islamic banking institutions. Furthermore, the understanding of the people of Pasirmunjul Sukatani Purwakarta Village regarding Islamic banks is still limited to mere awareness, and only a portion of the community has a clear understanding of Islamic banks. The lack of understanding among the community regarding Islamic banks is due to the limited information and education provided by Islamic banks. As a result, the potential for the development of Islamic banking in the area is hindered, and the community cannot optimally utilize Islamic financial services in accordance with the more ethical and inclusive principles of Islamic banking.